Grief and loss in old age: exploration of the association between grief and depression - Schladitz, Katja; Löbner, Margrit; Stein, Janine; Weyerer, Siegfried; Werle, Jochen; Wagner, Michael; Heser, Kathrin; Scherer, Martin; Stark, Anne; Kaduszkiewicz, Hanna; Wiese, Birgitt; Oey, Anke; et al. (Journal of affective disorders, 2021)
Background - The proportion of older adults is increasing due to demographic changes. Depression belongs to the most common mental disorders in late life. The loss of an emotionally significant person is a risk factor for the development of depression. The aim of this study is to analyze the association between depression and grief burden resulting from loss. Based on prior evidence, we examined loneliness as a possible mediator and social support as possible moderator of this association. - Methods - The cross-sectional analyses are based on a sample (N = 863) of study participants aged 75+ (M = 81.4 years, SD = 4.4, 62.2% female) with loss experience deriving from the multicenter prospective German cohort study AgeMooDe. Regression analyses (moderated mediation) were performed. - Results - With increasing age (β = 0.10, p = .005) and grief burden (β = 0.33, p <. 001) depression severity increased. There was an indirect mediating effect of loneliness on the correlation of grief burden and depression (b = 0.04, CI [0.03, 0.05]), but no moderating effect of social support on the correlation of grief burden and loneliness. People living alone had a significantly higher risk of depression, increased loneliness and lack of social support. - Limitations - Assessments were based on self-reporting and recorded dimensionally. The cross-sectional design limits conclusions about directions and causality of associations. Sampling bias cannot be completely excluded. - Conclusion - The study provides empirical evidence and a better understanding of the association between grief and depression among the very old and the mediating role of loneliness.